Exploring the influence of cognitive knowledge on sustainable business outcomes: A multi-dimensional analysis of the forms of knowledge - Nson , Yilkes Danladi; Polycarp, Kwarsen Linus; Andrew , Fazing Lohnap; Nathan , Awan (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: This study examines the influence of the four types of knowledge declarative, procedural, judgment, and wisdom knowledge—in achieving sustainable business outcomes in a dynamic and complex environment. It also highlights how these knowledge forms jointly shape decision-making, operational practices, and long-term sustainability among farmers in Plateau State. Methods: This study adopted a heuristic qualitative methodology. A total of 27 farmers in Mushere, Bokkos, Plateau State were interviewed through semi-structured interviews, field observations, and follow-up phone calls. The data were coded, and heuristics were induced over multiple rounds to generate insight and meaning. Results: The findings revealed that the four types of knowledge significantly influence sustainable business outcomes. Declarative knowledge provides factual information on sustainability concepts, while procedural knowledge translates these facts into practical actions that support sustainability objectives. Judgment knowledge offers strategic insight for making sound decisions, and wisdom knowledge ensures that decisions align with sustainability principles. Furthermore, the combination of these four forms of knowledge produces dynamic capabilities needed to achieve sustainable business outcomes. Conclusion: The study concludes that cognitive knowledge plays an essential and multifaceted role in achieving sustainable economic, social, environmental, and governance outcomes. Each type of knowledge contributes uniquely yet interdependently to sustainability practices among farmers in Plateau State. Limitation: This study used a heuristic qualitative methodology with a small sample size and was resource- and time-consuming due to extensive travel. It was also limited to examining four types of knowledge in Plateau State. Contribution: The study provides useful insights for business leaders, entrepreneurs, researchers, and policymakers on how the forms of knowledge facilitate sustainable business outcomes and strengthen dynamic capabilities.